Rabenosyn-5 and EHD1 Interact and Sequentially Regulate Protein Recycling to the Plasma Membrane - Naslavsky, Naava (The American Society for Cell Biology, 2004)
EHD1 has been implicated in the recycling of internalized proteins to the plasma membrane. However, the mechanism by which EHD1 mediates recycling and its relationship to Rab-family–controlled events has yet to be established. To investigate further the mode of EHD1 action, we sought to identify novel interacting partners. GST-EHD1 was used as bait to isolate a ∼120-kDa species from bovine and murine brain cytosol, which was identified by mass spectrometry as the divalent Rab4/Rab5 effector Rabenosyn-5. We mapped the sites of interaction to the EH domain of EHD1, and the first two of five NPF motifs of Rabenosyn-5. Immunofluorescence microscopy studies revealed that EHD1 and Rabenosyn-5 partially colocalize to vesicular and tubular structures in vivo. To address the functional roles of EHD1 and Rabenosyn-5, we first demonstrated that RNA interference (RNAi) dramatically reduced the level of expression of each protein, either individually or in combination. Depletion of either EHD1 or Rabenosyn-5 delayed the recycling of transferrin and major histocompatibility complex class I to the plasma membrane. However, whereas depletion of EHD1 caused the accumulation of internalized cargo in a compact juxtanuclear compartment, Rabenosyn-5-RNAi caused its retention within a dispersed peripheral compartment. Simultaneous RNAi depletion of both proteins resulted in a similar phenotype to that observed with Rabenosyn-5-RNAi alone, suggesting that Rabenosyn-5 acts before EHD1 in the regulation of endocytic recycling. Our studies suggest that Rabenosyn-5 and EHD1 act sequentially in the transport of proteins from early endosomes to the endosomal recycling compartment and back to the plasma membrane.